PENGARUH E-SERVICE QUALITY TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION PADA TOKO ON LINE BUKA LAPAK - Ahmad Irwansyah; Riko Mappadeceng (J-MAS (Jurnal Manajemen dan Sains), 2018)
Along with the development of an increasingly modern era, information technology is growing very rapidly. This is because all information required can be obtained easily and quickly via the internet. The development of the internet today not only serves as a medium of information, but the internet can also be utilized for the benefit of the business as a business online using a service-based website. The website-based services in many of the important components in it to achieve success in business, one of which is the quality of service (E-Service Quality). The company provides e-service quality the higher the customer then it will give rise to customer satisfaction, and in a long period of time will certainly generate customer loyalty. E-service quality is defined as the assessment and evaluation of the quality of the overall service delivery to consumers in a virtual market. Word of satisfaction or satisfaction derived from the Latin "satis" which means good enough, sufficient, and "facio" which means do or make. Contentment is a feeling happy or disappointed someone arising due to compare performance percepted products or results against the expectations of the customer. Customer loyalty or customer loyalty is the commitment of customers to a brand, stores or suppliers based on a very positive trait purchase in the long run. Buka Lapak is one of the shop on line which is currently enough many have customers in Indonesia. Although the Buka Lapak  already quite well-established as retailers on line but with a growing number of online stores are popping up then the Buka Lapak need to keep on doing the evaluation in order to remain able to compete with any other online store. From the analysis results can be summed up as that of E-service quality effect directly against customer loyalty, consumers Buka Lapak Indonesia, E-service quality positive effect towards customer satisfaction of consumers Buka Lapak, Indonesia E-service quality to customer loyalty through the customer satisfaction of consumers Buka Lapak Indonesia.